Effect Of Culture On Organizational Working: An Empirical Study On The Health Care Sector (International Journal of Scientific Research and Management (IJSRM), 2015)
Culture is the set of beliefs, attribute and values which the organization employees perceive. It is a set of values not visible but shared by the members of the organization. Every organization bears a culture essential for its growth and identity in the society. A conducive culture effects the working of the employees and hence the efficiency and effectiveness of the organization which eventually reflects on the outcome. Culture can be termed good or bad depending upon the perception of the workers. Culture is an important attribute for the overall development of the organization in today’s dynamic environment. Study on the developmental aspect of the organization is limited, particularly on the health care sector. The present study is focussed on the Culture of the health care sector taking into consideration three hospitals i.e. Fortis, SMHS and GMC. The study revealed that the health care sector has a satisfactory environment for OCTAPACE and both the genders perceive the culture of the hospitals to be conducive for working with females being more satisfied than males.